2012
DOI: 10.3945/ajcn.112.039974
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and the racial difference in the genotype 1 chronic hepatitis C treatment response

Abstract: Racial differences in vitamin D physiology or race-specific factors that modify the effects of vitamin D may affect the immune response to genotype 1 hepatitis C virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
0
27
2
Order By: Relevance
“…While some studies found an independent association between a higher baseline 25(OH)D level and SVR in HCV genotype 1/4/5 infection [5][6][7] and genotype 2/3 infection [8], others failed to find any relationship between baseline vitamin D level and treatment response [9][10][11]. These discordant results have led to uncertainty whether the baseline vitamin D level has any influence on SVR to PEG-IFN plus RBV antiviral therapy in chronic HCV infection.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…While some studies found an independent association between a higher baseline 25(OH)D level and SVR in HCV genotype 1/4/5 infection [5][6][7] and genotype 2/3 infection [8], others failed to find any relationship between baseline vitamin D level and treatment response [9][10][11]. These discordant results have led to uncertainty whether the baseline vitamin D level has any influence on SVR to PEG-IFN plus RBV antiviral therapy in chronic HCV infection.…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, 11 studies, comprised of 7 published articles [5][6][7][8][9][10][11] and 4 conference abstracts [20][21][22][23], involving 2605 patients with chronic HCV infection, were included in the meta-analysis (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…Three studies (Amanzada et al, 2013;Kitson et al, 2013;Petta et al, 2013) included patients with chronic hepatitis C genotype 1 infection, one (Lange et al, 2011) with chronic hepatitis C genotype 1, 2, or 3-infection, one (White et al, 2013) with chronic hepatitis C genotype 1, 2, 3, or 4-infection, and one (Arteh et al, 2010) did not specify the kind of HCV type. Four studies (Baur et al, 2012;Corey et al, 2012;Weintraub et al, 2012;Ladero et al, 2013) were excluded because they did not report usable data. One study (Petta et al, 2010) was excluded because it reported on the same author.…”
Section: G1mentioning
confidence: 99%
“…age and sex), IFNL4 genotype, which was not available in previous studies, and a comprehensive suite of systematically measured clinical markers of liver disease. Moreover, only one previous study considered the association of vitamin D and SVR separately among African Americans [50]; this cross-sectional study by Weintraub et al, which included 106 African Americans and 65 whites who were chronically infected with HCV genotype 1, did not adjust for potential confounding factors and pretreatment serum was not available for all patients. Similar to our findings, Weintraub et al, found no evidence of an association between vitamin D status and SVR following PEG-IFNα/RBV therapy among African Americans.…”
Section: Discussionmentioning
confidence: 99%